On the use of under sleeper pads in transition zones at railway underpasses: experimental field testing - Paixão, A. (2015)
The railway track at transition zones to bridges or to other structures usually requires considerably more interventions to maintain the same open track service quality and safety levels. Under sleeper pads (USP) have been reported to contribute to reduce degradation and frequency of maintenance operations in open ballasted tracks, and recent numerical studies have suggested its use in transition zones. In this study, the inﬂuence of using USP at transition zones to underpasses was investigated. The structural behaviour of two transitions to similar box culverts was compared. USP were added to the sleepers in one of the transitions. Track characterisation using non-destructive tests is presented and analysed. Measurements of track response from passing trains are also presented and discussed. Results indicate that USP inﬂuence the dynamic behaviour of the track, increasing its vertical ﬂexibility and amplifying both rail displacements and sleeper accelerations.